2022
DOI: 10.3390/nano12193287
|View full text |Cite
|
Sign up to set email alerts
|

A Room Temperature ZnO-NPs/MEMS Ammonia Gas Sensor

Abstract: This study uses ultrasonic grinding to grind ZnO powder to 10–20-nanometer nanoparticles (NPs), and these are integrated with a MEMS structure to form a ZnO-NPs/MEMS gas sensor. Measuring 1 ppm NH3 gas and operating at room temperature, the sensor response for the ZnO-NPs/MEMS gas sensor is around 39.7%, but the origin-ZnO powder/MEMS gas sensor is fairly unresponsive. For seven consecutive cycles, the ZnO-NPs/MEMS gas sensor has an average sensor response of about 40% and an inaccuracy of <±2%. In the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…11C). 94 Gas sensors to detect various gases driven by a similar principle have been frequently reported. 95–98 Simultaneous detection with a single sensor of multiple gases (H 2 and CO 2 ) has also been achieved using the sensitivity difference of gases.…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…11C). 94 Gas sensors to detect various gases driven by a similar principle have been frequently reported. 95–98 Simultaneous detection with a single sensor of multiple gases (H 2 and CO 2 ) has also been achieved using the sensitivity difference of gases.…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…We detected the ammonia vapor in a mediumhumidity environment, hence oxygen ions react with ammonia on the surface of the ZnO thin lms and water ions participate in the reaction [44]. The reactions between oxygen ions and ammonia could be written as [40,44]:…”
Section: Fig 2 3d Afm Image Of Zno Thin Lmmentioning
confidence: 99%
“…Several gas sensors based on SMOs such as zinc oxide (ZnO), zinc gallate (ZnGa 2 O 4 ), tin oxide (SnO 2 ), nickel cobaltite (NiCo 2 O 4 ), zinc stannate (Zn 2 SnO 4 ), copper oxide (CuO), etc., possess some good properties such as precision, low cost, small dimensions, long-term stability and environmental friendliness; because of these properties, SMOs could be considered the primary candidates for the detection of toxic gases as well in photo-catalysis, etc. [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Plenty of research has shown that some complex metal oxides have been widely used as gas sensors in the last decades.…”
Section: Introductionmentioning
confidence: 99%